Proxy assessment of quality of life in patients with prostate cancer: how accurate are partners and urologists? - Pearcy, R (The Royal Society of Medicine, 2008)
OBJECTIVES: To assess the ability of partners and clinicians to make proxy judgements on behalf of patients with prostate cancer relating to selection of life priorities and quality of life (QoL). DESIGN: 47 consecutive patients with histologically proven adenocarcinoma, and their partners, were recruited. The partners were asked to assess, by proxy, the QoL of the patient by completion of a series of interview-led questionnaires assessing global QoL (SEIQoL-DW), health-related QoL (FACT-P) and overall QoL (visual analogue score [VAS]). The patients' clinicians were asked to complete the SEIQoL-DW and VAS by proxy as soon as possible after a consultation with the patient. SETTING: Patients with histologically proven adenocarcinoma, their partners and their clinicians. MAIN OUTCOME MEASURES: Proxy scores for SEIQoL-DW, FACT-P and VAS, as provided by partners and clinicians. RESULTS: 25 partners made a proxy assessment of the patients. The results showed that partners were able to select similar QoL cues to those of the patients (Spearman-Rank correlation 0.89). Comparison of the QoL scores obtained from patients and partners in proxy using the questionnaires showed no statistically significant difference (paired t-test). Urologists were poor predictors of areas of life (cues) that were important to their patients. The doctors overemphasized the importance of survival, postoperative complications, urinary symptoms, sexual ability, activities of daily living and finance, but underestimated the importance of wife, family, home and religion. Comparison of the QoL scores obtained from patients and urologists by proxy showed a significantly lower score when assessed by urologists using the SEIQoL-DW questionnaire. CONCLUSIONS: Partners are able to accurately assess, by proxy, the areas of life that are of importance to patients. Clinicians, however, who are charged with making decisions on behalf of patients, are very poor judges of their patients' life priorities and QoL. This illustrates that conventional views held by most doctors regarding the priorities patients set themselves when planning treatment should be called into question and consequently suggests that the way in which doctors and patients arrive at treatment decisions must be reviewed.